2020
DOI: 10.3350/cmh.2020.0032
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for the management of chronic hepatitis B

Abstract: Hepatitis B virus (HBV) cannot be eliminated completely from infected hepatocytes because of the presence of intrahepatic covalently closed circular DNA (cccDNA). As chronic hepatitis B (CHB) can progress to cirrhosis and hepatocellular carcinoma (HCC), it is important to manage CHB to prevent HCC development in high-risk patients with high viral replicative activity or advanced fibrosis. Serum biomarkers are noninvasive and valuable for the management of CHB. Hepatitis B core-related antigen (HBcrAg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 138 publications
(329 reference statements)
0
97
0
1
Order By: Relevance
“…Although serum DKK-1 has been reported as a useful biomarker in several cancers, its clinical implications are controversial. For example, serum DKK-1 levels are high in patients with cervical, endometrial cancer, and hepatocellular carcinoma, when compared to controls [20][21][22]. In contrast, some studies have shown that DKK-1 expression is downregulated in colorectal cancer, brain tumor, and papillary thyroid cancer [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although serum DKK-1 has been reported as a useful biomarker in several cancers, its clinical implications are controversial. For example, serum DKK-1 levels are high in patients with cervical, endometrial cancer, and hepatocellular carcinoma, when compared to controls [20][21][22]. In contrast, some studies have shown that DKK-1 expression is downregulated in colorectal cancer, brain tumor, and papillary thyroid cancer [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…To date, one-third of the world’s population, which accounts for approximately 2 billion people, has been infected with HBV, and more than 200 million people suffer from CHB [ 1 ]. Individuals with CHB are at a greater than 100-fold increased risk of developing advanced liver diseases, including cirrhosis and HCC [ 2 , 3 ]. Therefore, HCC remains among the leading causes of cancer death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel biomarkers have been proposed to reflect the intrahepatic HBV reservoir [ 17 , 18 ], providing information on the clinical evolution and therapeutic outcome of HBV infection. Among them, serum HBV-RNA measures the amount of viral particles containing pre-genomic RNA molecules lacking the reverse transcriptase process [ 19 ].…”
Section: Introductionmentioning
confidence: 99%